Entrepreneurial Orientation and Entrepreneurial Intention among Business Students: Evidence from Pokhara - Kripa Kunwar; Resam Lal Poudel; Surya Bahadur G.C.; Umesh Singh Yadav (Journal of Business and Social Sciences, 2025)
Drawing on the theory of planned behavior, this study examines whether entrepreneurial orientation influences the entrepreneurial intention of business students. The study adopted the quantitative approach. Data were collected from 207 university-level business students in Pokhara by using the validated questionnaire. A convenience sampling method was used to choose the respondents. The study revealed that students have a strong entrepreneurial orientation and entrepreneurial intention. In addition, individual traits such as risk-taking, and proactiveness are significant predictors of entrepreneurial intention. However, there is no effect of innovativeness behavior on shaping the entrepreneurial intention of the student. The study found that an individual’s entrepreneurial orientation strengthens the entrepreneurial intention of the student. This study offers useful practical implications to policymakers and academicians in empowering youth and addressing the issues of unemployment. It also contributes to the scant literature on entrepreneurial intention in the context of emerging economies.